Comparison of photocatalytic activity and cyclic voltammetry of zinc oxide and titanium dioxide nanoparticles toward degradation of methylene blue - Fatin, S.O.; Lim, H.N.; Tan, W.T.; Huang, Nay Ming (Electrochemical Science Group, 2012)
We report on the photocatalytic degradation of methylene blue (MB) solution using commercial ZnO and TiO2 (P25) photocatalysts, in the form of slurry and immobilized on glass slides, under ultraviolet (UV) and solar irradiations. The average particle sizes of ZnO and P25 were 100 nm and 30 nm, respectively. Under both the irradiations, the photocatalytic activities of ZnO and P25 slurry resulted in better photocatalytic performance than the immobilized photocatalysts. Interestingly, ZnO showed better degradation capability in comparison to P25 under the solar irradiation. This result revealed that solar light provided a good source of energy to degrade MB in the presence of ZnO. The cyclic voltammetry analysis suggested that the photocatalysts possessed different mechanisms for the degradation of MB. The potential of immobilizing photocatalysts without compromising their performance may lead to easy handling of these materials, resulting in expanding their applications, for example, as a photoanode for photoelectrochemistry.